Phytochemical analysis, antioxidant, anti-inflammatory and enzyme inhibitory activities of bean pear (Pyrus calleryana fruit) - Zhao, Huan; Wang, Qinqin; Yang, Lanlan; Ran, Yuanquan; Hu, Qiong; Hong, Yi; Tian, Minyi (Frontiers in Plant Science, 2025)
Pyrus calleryana fruit (bean pear) is processed into fruit wine and used in traditional Chinese medicine. The present study reported phytochemical constituents, antioxidant, anti-inflammatory, and enzyme inhibitory activities of P. calleryana fruit water extract (WE) and ethanol extract (EE). In the P. calleryana fruit WE and EE, 63 compounds were identified using UHPLC-Q-Orbitrap-MS analysis, including 23 phenols, 13 flavonoids, 14 terpenoids, and 13 other types of compounds. In the antioxidant activity, WE and EE showed marked free radical scavenging effects on both ABTS (2.33 ± 0.15 μg/mL and 2.23 ± 0.15 μg/mL, respectively) and DPPH (5.93 ± 0.55 μg/mL and 7.07 ± 0.23 μg/mL, respectively), especially, their scavenging effects on DPPH free radicals were superior or equivalent to that of BHT (7.47 ± 0.47 μg/mL). In LPS-induced RAW264.7 cells, P. calleryana fruit WE and EE remarkably inhibited the secretion of inflammatory factors, and the inhibitory effect of WE on the release of IL-6, NO, and PGE2 was superior or equivalent to that of EE. Interestingly, P. calleryana fruit WE and EE exhibited potent inhibition on α-glucosidase (0.60 ± 0.09 μg/mL and 0.48 ± 0.09 μg/mL, respectively) and tyrosinase (210.11 ± 2.59 μg/mL and 45.35 ± 0.96 μg/mL, respectively), which were superior to their respective positive controls acarbose (302.57 ± 22.09 μg/mL) and arbutin (243.07 ± 15.91 μg/mL). Our findings suggested that P. calleryana fruit WE and EE possess significant antioxidant, anti-inflammatory, α-glucosidase, and tyrosinase inhibitory properties. Thus, P. calleryana fruit has great potential for application in functional food products.